On the Distributive Costs of Drug-Related Homicides - Nicolas Ajzenman; Sebastian Galiani; Enrique Seira (Inter-American Development Bank (IDB), 2014)
There are few reliable estimates of the effects of violence on economic outcomes. This study exploits the manifold increase in homicides in 2008-2011 in Mexico resulting from its war on organized drug traffickers to estimate the effect of drug- related homicides on housing prices. Using an unusually rich dataset that provides national coverage on housing prices and homicides and exploits within- municipality variation, the study finds that the burden of violence affects only the poor. An increase in homicides equivalent to one standard deviation leads to a 3 percent decrease in low-income housing prices. Moreover, the effect on housing prices of long-term increases in crime is 40 percent larger.
Keywords: I3; K4; 330